Self-Learning Strategy in Teaching Speech Skills to Face COVID 19/ Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø°Ø§ØªÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ù…ÙˆØ§Ø¬Ù‡Ø© COVID 19 - Mufidah, Nuril; Mohammad Idrees, Mohammad Umar Hafiz (Ijaz Arabi Journal of Arabic Learning, 2020)
Education has new requirements for teaching the individual how to teach himself by himself to continuous education and lifelong learning. Self-regulated learning is one of the central axes to accommodate these rapid and successive developments, mainly when global crises occurred. Self-regulated learning can help students become independent learners to achieve their goals. It can also reach distinctive performance, especially for developing the linguistic skills represented in speech skills, whose impact appears daily through effective human communication, whether oral or written communication. The research technique used is a literature study. This study aims to shed light on the self-regulated learning strategy to developing speaking skills, and its implications, in terms of the effects of the Corona pandemic (COVID 19) on various educational activities. Also, clarifying what is meant by speech and developing his skills, and knowing the learning strategy and how to use it in developing speech skills. The problem-solving strategy is considered one of the essential self-learning strategies. The learner independently develops his skills and knowledge by searching for practical solutions to real problems by relying on oneself. Self-regulated learning is considered a successful method for developing speech skills. The student's performance as the independent learner can be measured through his various daily social activities in order to help him evaluate his strategies followed and choose the most difficult ones to achieve the goals of the self-education process, and to reach the required level of language skill.